P²URE: Proactive and Probabilistic Uncovered Neighbor-Aware Relay-Selection Method in Multi-Hop FANETs - Lee, Yerin; Jeon, Jimin; Choi, Jungwook; Park, Soobum; Jung, Bang Chul; Lee, Howon (IEEE Access, 2024)
Recently, multi-hop flying ad hoc networks (FANETs) have received considerable attention because of their various advantages, such as ease of deployment, scalability, cost, and latency reduction. However, FANETs still encounter serious problems such as a highly dynamic network topology and the limited on-board battery of unmanned aerial vehicles (UAVs). Thus, to increase the coverage probability while reducing unnecessary packet transmissions, realizing efficient and effective relay selection is important. To resolve these issues, this paper proposes a proactive and probabilistic uncovered neighbor-aware relay selection (P2URE) method that considers FANET's topological dynamics. Specifically, the relay decision factor to identify relay UAV candidates and the probabilistic relay decision to reduce coverage overlaps and minimize redundant packet transmissions are devised. Through extensive simulations, it has been validated that the proposed P2URE method surpasses the benchmark methods in terms of the total number of transmissions, coverage probability, and energy efficiency. This superiority is observed across various network dynamics resulting from variations in the UAV density, speed, neighbor-information update period, and delay interval.
Keywords: Ad-hoc networks; Aerial relay selection; Aerial vehicle; Decision factors; Flying ad hoc network; Information updates; Neighbor information update; Relay decision factor; Relay selection; Uncovered neighbor; Unmanned aerial vehicle; aerial relay selection; flying ad hoc network; neighbor information update; relay decision factor; Uncovered neighbor; unmanned aerial vehicle